Tourism in the City 2016
DOI: 10.1007/978-3-319-26877-4_18
|View full text |Cite
|
Sign up to set email alerts
|

Venice Reshaped? Tourist Gentrification and Sense of Place

Abstract: This paper is aimed to explore the role of tourism in reshaping historical cities, particularly into forms of cosmopolitan consumption. New mobility paradigms seem to merge production and consumption patterns of tourists and residents, all influenced by similar gazing and performing places. The iconic case of Venice shows patterns of staged authenticity, reconstructed ethnicity, and economy of subordination. Drivers to visit Venice include experiences in a setting that is densely characterized by cultural heri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 17 publications
(11 reference statements)
0
12
0
2
Order By: Relevance
“…Like other studies have shown (e.g. Doxey, 1975;Minoia, 2017), growing tourism, and particularly fast tourism can produce deeper residential issues and conflicts, even starting by occasional disturbances on specific walkways. No potential conflict of interest was reported by the authors.…”
Section: Resultsmentioning
confidence: 53%
“…Like other studies have shown (e.g. Doxey, 1975;Minoia, 2017), growing tourism, and particularly fast tourism can produce deeper residential issues and conflicts, even starting by occasional disturbances on specific walkways. No potential conflict of interest was reported by the authors.…”
Section: Resultsmentioning
confidence: 53%
“…These are often small cities that became economically dependent on tourism traffic. Examples of Dubrovnik [32] and Venice [6,27,99] presented here, and also places such as Palma de Majorca [100], prove that the situation of those destinations is extremely complicated. In big cities that are not dependent on tourism, it is possible to keep only the supportive function of tourism in economic development while limitations for tourists, which may make them less attractive for them in favor of citizens' quality of life, can be introduced.…”
Section: Limitationsmentioning
confidence: 74%
“…Instead of involving citizens and policymakers and looking at collaboration between various social groups, the possible (and desirable) dialogue about tourism management is moving towards an almost critical position rather than towards a shared field. In such a field, proposals that engage marginalized groups in a participatory and ethical production of solutions and in sharing benefits can improve the situation [35][36][37][38][39]. The debate about the tangible and intangible impacts of tourism on the city's social spaces is also associated with increasing frictions between inhabitants and tourists, as highlighted by the emergence of urban social movements, organizations, and associations in many European destinations [6,26].…”
Section: Venice: the Flooded Citymentioning
confidence: 99%